Communicating Through a Pandemic A Chronicle of Experiences, Lessons Learned, and a Vision for the Future. - Burke-Garcia, Amelia (Milton : Productivity Press, 2022)
Outbreaks, epidemics, and pandemics are nothing new. Over the last several decades, we have been through numerous--Zika, Ebola, H1N1. The COVID19 pandemic, however, has challenged us like never before. During this time, we have struggled to work remotely, to balance work and children's school schedules, and to manage finances in the face of lost or furloughed jobs. We have worried about our loved ones getting sick and being able to support themselves, and we have faced the loneliness that comes with social distancing. It has affected us individually and globally--but we have not all experienced this pandemic in exactly the same way. Some communities have been hit harder in terms of sickness and death rates from COVID19. Many have felt the economic pressures of the pandemic more acutely. Still others have struggled disproportionately with the mental health impacts. Context has mattered in this pandemic. There is one common thread that runs through everything we have experienced though: the role that communication has played in managing this pandemic. Whether we are talking about communication about the virus and mitigation strategies, communication between friends and family, the urgent crisis resulting in mis- and dis-information, our complex and diffuse media environment, or new workplace communication strategies, communication has been front and center in this pandemic. The role of communication has been integral to the success and failure of our ability to respond and adapt to and begin to recover from this pandemic--as individuals, collectively as communities, and as countries. As a result, issues such as preparedness, misinformation, literacy and comprehension of virus and vaccine science, health equity and mental health have all gained increased awareness during this time. This book unpacks the many and varied roles that communication has played over the course of this pandemic, in order to help public health professionals, marketers and health communicators, and policymakers alike to understand what we have been through, what has worked well, and what we have struggled with. It will help us learn from our experiences, so we communicate through pandemics more successfully in the future.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Industries / Media & Communications Industries; BUSINESS & ECONOMICS / Business Communication / General; Communication in public health; Communication -- Social aspects; COVID-19 Pandemic, 2020- -- Social aspects